Peningkatan Kualitas Pendidikan dan Pelestarian Lingkungan di Kampung Njawani - Adiyatama, Bima Prayoga; Gunawan, Christian Tedric; Saputra, Dandra Wahyu; Kristiawan, Davar Abednego; Romanzah, Dede; Hazim, Dhimas Aziz Ahmad; Pardomuan, Dimas Marchelino; Safitri, Elsa; Widiasari, Meirliana; Hartono, Otniel Oktavianus; Sulistyaningrum I, Cicilia Dyah (Yayasan Daarul Huda Kruengmane, 2024)
Njawani Village, located in Banjarsari District, Surakarta Regency, is one of the villages that has a wealth of culture and traditions that are highly valued by its people. This village is known for its various traditional art performances such as dances, gamelan, and wayang kulit performances. The main theme of this KKN program is